SYNTHESIS AND CHARACTERIZATION: COMPOSITE OF GRAPHENE OXIDE BASED PALM KERNEL SHELL WASTE WITH FE3O4 - Bernadeta Ayu Widyaningrum; Dita Apriani; Putri Amanda; Ismadi Ismadi; Sutanto Sutanto (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2021)
SYNTHESIS AND CHARACTERIZATION: COMPOSITE OF GRAPHENE OXIDE BASED PALM KERNEL SHELL WASTE WITH Fe3O4. In this study, GO-Fe3O4 were fabricated by co-precipitation technique and the graphene oxide (GO) were synthesized from an agricultural biomass, palm kernel shell, via Hummer’s method. Field Emission Scanning Electron Microscopy and Energy Dispersive Spectrum (FESEM-EDS), Fourier Transform Infra-Red (FT-IR) spectroscopy, X-Ray Diffractometer (XRD), and Raman spectroscopy were used to analysis the successful attachment of Fe3O4 onto the surface of GO. Morphology observation showed that Fe3O4 were heterogeneously deposited on the surface of GO. FT-IR spectra shows peak that incorporated to oxygenated functional groups and sharp peak at 586 cm-1 confirmed to lattice absorption of Fe3O4. The percentage of composition of GO-Fe3O4 was characterized by energy dispersive spectroscopy and the results also confirmed in XRD exhibits similar properties with JCPDS 19-0629 for magnetite more dominant than GO. From Raman spectroscopy analysis shows that 1343.82 cm-1 (D-band) and 1584.62 cm-1 (G-band) and 2698 cm-1 (2D-band) indicates GO and GO-Fe3O4 were successfully synthesized.